Pengenalan Tembang Dolanan melalui Dongeng Interaktif bagi Siswa Sekolah Indonesia Johor Bahru (SIJB) - Juniarti, Anugrah Putri; Pairin, Udjang; Surana, Surana; Wijoyanto, Danang; Istantiani, Meinita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to introduce Javanese folk songs to students at the Indonesian School of Johor Bahru (SIJB) through interactive online and face-to-face storytelling. The online learning sessions were conducted via Zoom from October 6–21, 2024 (ten sessions) and face-to-face on October 22, 2024. The fairy tale titled “Kancil lan Pak Tani” was modified to include the song Gundhul gundhul Pacul, with the hope of strengthening understanding of cultural and moral values. Observations showed excellent student enthusiasm, the ability to sing the song in 10 sessions, and an increase in understanding of moral meanings and Javanese vocabulary. Partner teachers stated that this activity enriched cultural learning and supported plans for a performance at the “Wonderful Nusantara” event in Malaysia. These findings indicate that interactive storytelling-based cultural learning is an effective strategy in a cross-border context. Recommendations for further activities include the development of digital modules and training in other folk songs.